Well-differentiated gall bladder hepatoid carcinoma producing alpha-fetoprotein: a case report - Kao, Ching-Yun (BioMed Central, 2009)
INTRODUCTION: Gall bladder carcinoma is rare, and metastatic gall bladder carcinoma from hepatocellular carcinoma has been reported in only a few patients. CASE PRESENTATION: We present a 73-year-old man with a history of hepatitis B virus-related liver cirrhosis and hepatocellular carcinoma. He received transcatheter arterial chemoembolization, and was diagnosed to have an alpha-fetoprotein producing gall bladder tumor with intraluminal growth. Open cholecystectomy was performed. Pathologic examination of the lesion revealed a well-differentiated hepatoid carcinoma. The lesion was thought most likely to be a metastatic lesion from previous hepatocellular carcinoma. His alpha-fetoprotein level dropped to normal levels five months after the surgery. CONCLUSION: This unusual intraluminal growing tumor proved to be a well-differentiated hepatoid carcinoma, most likely a metastatic lesion from previous hepatocellular carcinoma. This case reminds clinicians that in looking for likely hepatocellular carcinoma recurrence, when no detectable hepatic lesion can account for an elevated alpha-fetoprotein level, the gall bladder should be included in the search for the site of metastasis.